FOOD SECURITY STATUS OF ARTISANAL FISHING HOUSEHOLDS IN OGUN WATERSIDE LOCAL GOVERNMENT AREA OF OGUN STATE - OYETADE, O. P.; BAMIDELE, N.A.; OJEBIYI, W. G.; OYEBAMIJI, B. A.; TAIWO, I. O.; ALE, O. A.; OLAITAN, K. A. (Nigerian Journal of Fisheries, 2022)
Majority of the fishing households in Nigeria has been associated with low food security and malnutrition, therefore, this study examine the nutritional status of fishing households in Ogun waterside local government area of Ogun state. Three communities within the selected local government were purposively selected and random selection of households, they are: Agbalegiyo (26), Ilamo (22) and Iwopin (37). A total of 85 fishing households were accessed through the use of validated interview guide. Data were analyzed using descriptive statistics and regression analysis. 45.9% of the fishers had a mean age of 50.64±12.11, 85.9% were male and married (89.4%). 62.4% of the fishers were food secure. Also, 15.3% and 5.9% indicated high food security and marginal food security respectively. Years spent in school (ꞵ = 0.032, P < 0.01), number of dependent (ꞵ = 0.970, P ≤ 0.01) and age of respondents were significant to food security index. The study concluded that years spent in school, number of household dependent and age has great influence on the food security status of the fishing households. Livelihood improvement through income diversification was recommended.